Identity Leadership, Social Identity Continuity, and Well-Being at Work During COVID-19 - Krug, Henning; Haslam, S. Alexander; Otto, Kathleen; Steffens, Niklas K. (Frontiers in Psychology, 2021)
The COVID-19 pandemic has led to widespread remote working that has posed significant challenges for people’s sense of connection to their workplace and their mental health and well-being. In the present work, we examined how leaders’ identity leadership is associated with the well-being of employees in the context of the COVID-19 pandemic. Specifically, we examined how both leaders’ and team members’ identity leadership is associated with employees’ social identity continuity, and through this with their job satisfaction, burnout and loneliness at work. Employees (N = 363) participated in a field study during the COVID-19 pandemic, completing measures of their leader’s and team members’ identity leadership (i.e., entrepreneurship and impresarioship), social identity continuity, job satisfaction, burnout, loneliness at work. Results revealed that to the extent that employees perceived greater social identity continuity, they were more satisfied with their work and felt less lonely. Furthermore, mediation analyses revealed indirect effects of team members’ identity entrepreneurship on job satisfaction and loneliness via an increase in social identity continuity. To foster their employees’ health and well-being, organizations should focus on maintaining a sense of ‘we-ness’ at work during times of crises and not only rely on their formal leaders to do so but to use the capacities of all organizational members. The findings underline the importance of identity leadership and social identity continuity for the well-being of employees in times of the current crisis.